SUBCONTRACTORS SATISFACTION ANALYSIS ON PURCHASER’S SERVICE QUALITY WITH SERVQUAL METHODE, CUSTOMER SATISFACTION INDEX (CSI) METHODE, AND IMPORTANCE PERFORMANCE ANALYSIS (IPA) METHODE IN SHIPYARD AT SURABAYA - Avicena Fajri Romadhon; Devina Puspita Sari; Irma Rustini Aju (Proceeding Maritime Business Management Conference, 2024)
In the last 3 (three) years, the number of Sub Contractors at the Shipyard in Surabaya has decreased. It can be caused by many things, one being the service quality received by subcontractors. This research aimed to find service satisfaction scores, find attributes that need improvement and find the solutions for improving service quality at Shipyard in Surabaya. This research uses the Servqual method, the Customer Satisfaction Index (CSI) method, and the Importance Performance Analysis (IPA) method. The Servqual method shows 18 (eighteen) variables have a negative gap (under expectation) and 4 (four) variables have a positive gap (above expectation), with the CSI method showing the percentage of customer satisfaction is around 67% means the subcontractors are satisfied, with IPA methode show eight service satisfaction attributes need to be fixed, they are X6 (information), X10 (contract realization), X12 (help access), X14 (meeting access with purchaser), X15 (purchaser responsiveness), X17 (promise realization), X19 (contrac’s status), X21 (subcontractor application realization). Hopefully, this research will be useful in increasing the service quality of the Shipyard at Surabaya.